2009
DOI: 10.1682/jrrd.2009.03.0035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of He-Ne laser radiation on healing of osteochondral defect in rabbit: A histological study

Abstract: Abstract-This study examined the influence of low-level laser therapy (LLLT) on the healing of a large osteochondral defect in rabbits. An osteochondral defect with 5 mm diameter was surgically induced in the right femoral patellar groove of 48 adult male rabbits. They were divided into a control and an experimental group. The rabbits were treated at 2, 4, 8, and 16 weeks after surgery, with six rabbits in each study period being tested at each biweekly period. The experimental group received LLLT with a heliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It was shown that the healing of the lesion was faster at week 2 after laser treatment than for control. A study by Bayat et al 55 examined the infl uence of LILT (using a He-Ne laser) on the healing of a large (5 mm in diameter) osteochondral defect in rabbits. It was shown that laser radiation diminished the rate of healing during the fi rst 2 weeks, and accelerated regeneration over a longer period of observation (4 and 16 weeks).…”
Section: Lilt Studies In Orthopaedicsmentioning
confidence: 99%
“…It was shown that the healing of the lesion was faster at week 2 after laser treatment than for control. A study by Bayat et al 55 examined the infl uence of LILT (using a He-Ne laser) on the healing of a large (5 mm in diameter) osteochondral defect in rabbits. It was shown that laser radiation diminished the rate of healing during the fi rst 2 weeks, and accelerated regeneration over a longer period of observation (4 and 16 weeks).…”
Section: Lilt Studies In Orthopaedicsmentioning
confidence: 99%
“…6 Different laser types with different wavelengths including Helium-Neon (He-Ne) and Diode (gallium-aluminium-arsenide, gallium-arsenide) have been used at different doses and different treatment schedules for LLLT. 7,8 In recent studies, the Ga-Al-As type of diode lasers has been shown to be more effective in biostimulation than He-Ne lasers due to the higher penetration ability into the deep tissues. 9 The dose-dependent…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was also mentioned that by triggering vascularization and inflammatory response, it facilitates bone matrix production as well (30). However, in certain studies, although the positive effect of LLLT on hard and soft tissue recovery was demonstrated, it was observed that the estimated effect on recovery was not seen or the laser had negative effects (31)(32)(33). In our study, we observed that MDA and CAT levels in the liver of the rats in the groups where mandibular defect + laser were applied both for 7 and 21 days were similar to that of the mandibular defect group (P<0.05).Under certain conditions where free radicals are produced extensively such as inflammation or trauma, endogenous antioxidants could be insufficient.…”
Section: Discussionmentioning
confidence: 99%